The Potential of Sukuk for Financing Oil and Gas Sector in Nigeria - Tijjani Muhammad; Haruna Tijjani Haruna (Universitas Muhammadiyah Yogyakarta, 2022)
Nigeria has promising investment opportunities in the up and downstream sectors of the oil and gas industry that need financing. In the upstream, there are an estimated 37.2 Billion proven oil reserves and 182 Trillion cubic feet of natural gas. New investment opportunities are being developed, and individual and organizational investors need to finance their activities by purchasing drilling equipment and financing their infrastructures and storage facilities. Sukuk financing became a potential investment opportunity that could significantly address the upstream and downstream oil and gas sector and restore the glory of refineries in the country. There are currently three petroleum refineries in Nigeria with a stated capacity of 438 750. Perhaps the refineries are obsolete and bedeviled by poor management and turnaround maintenance due to the lack of funding. The study examines the potential of Sukuk financing oil and gas in the sector in Nigeria. The study employed Structural Equation Modeling to test the respondents' perspectives on the proposed model. Findings predict that the government may diversify and look for an alternative for funding that attracts more investors to participate in Sukuk financing. Future research is encouraged to use quantitative assessment methods to assess funding priorities between the Upstream, middle and downstream petroleum sectors.